Current Understanding of Flavonoids in Cancer Therapy and Prevention - Mohd Farhan; Asim Rizvi; Mohammad Aatif; Aamir Ahmad (Metabolites, 2023)
Cancer is a major cause of death worldwide, with multiple pathophysiological manifestations. In particular, genetic abnormalities, inflammation, bad eating habits, radiation exposure, work stress, and toxin consumption have been linked to cancer disease development and progression. Recently, natural bioactive chemicals known as polyphenols found in plants were shown to have anticancer capabilities, destroying altered or malignant cells without harming normal cells. Flavonoids have demonstrated antioxidant, antiviral, anticancer, and anti-inflammatory effects. Flavonoid type, bioavailability, and possible method of action determine these biological actions. These low-cost pharmaceutical components have significant biological activities and are beneficial for several chronic disorders, including cancer. Recent research has focused primarily on isolating, synthesizing, and studying the effects of flavonoids on human health. Here we have attempted to summarize our current knowledge of flavonoids, focusing on their mode of action to better understand their effects on cancer.